Modern war and the utility of force challenges, methods and strategy - Angstrom, Jan; Duyvesteyn, Isabelle (Cass military studies, 2010)
This book investigates the use and utility of military force in modern war. After the Cold War, Western armed forces have increasingly been called upon to intervene in internal conflicts in the former Third World. These forces have been called upon to carry out missions that they traditionally have not been trained and equipped for, in environments that they often have not been prepared for. A number of these "new" types of operations in allegedly "new" wars stand out, such as peace enforcement, state-building, counter-insurgency, humanitarian aid, and not the least counter-terrorism. The success rate of these missions has, however, been mixed, providing fuel for an increasingly loud debate on the utility of force in modern war. This edited volume poses as its central question: what is in fact the utility of force? Is force useful for anything other than a complete conventional defeat of a regular opponent, who is confronted in the open field?